Causal effects of gallstone disease on risk of gastrointestinal cancer in Chinese - Pang, Y; Lv, J; Kartsonaki, C; Guo, Y; Yu, C; Chen, Y; Yang, L; Bian, Z; Millwood, IY; Walters, RG; Li, X; Zou, J; et al. (Springer Nature, 2021)
Background: Gallstone disease (GSD) is associated with a higher risk of gastrointestinal (GI) cancer. However, it is unclear whether the associations are causal.